Characterization of memory and attention in school children with chronic malnutrition - Paredes Arturo, Yenny Vicky (Universidad y Salud, 2013)
Objective: To characterize the memory and attention functions in a group of 70 school children, 35 of them diagnosed with malnutrition. Methods: This is a quantitative research, with an ex post facto prospective simple design. The population was a group of 70 school children, 35 subjects were part of the control group (without malnutrition) and 35 for case group (with chronic malnutrition). Cognitive processes such as attention and memory were evaluated through various neuropsychological tests. Results: Better performance was found in the case group in the subtest “direct digits” and total score; however, there were no statistically significant differences between the groups in relation to the scores obtained with tests that measured attention. Regarding the memory function, the case group had a significantly lower performance in logical memory compared with the control group. Conclusions: The group case evidences some difficulties related to logical memory, which may influence academic learning with narrative content subjects when they focus on the dimension of memorization; however, this deficit seems to be offset by sequential processing and short term memory.